Poetries - politics : a celebration of language, art, and learning - DeLosSantos, Jenevieve (Book collections on Project MUSE., 2023)
"Poetries - Politics: A Celebration of Language, Art, and Learning celebrates the best of innovative humanities pedagogy and creative graphic design. Designed and implemented during a time of political divisiveness, the Poetries - Politics project created a space of inviting, multilingual walls on the Rutgers campus, celebrating diversity, community, and cross-cultural exchange. This book, like the original project, provides a platform for the incredible generative power of student-led work. Essays feature the perspectives of three students and professors originally involved in the project, reflecting on their learning and exploring the works they selected for the original exhibition. The essays lead to a beautifully illustrated catalogue of the original student designs. Reproduced in full color and with the accompanying poems in both their original language and a translation, this catalogue commemorates the incredible creative spirit of the project and provides a new way of contemplating these great poetic works"--